Sistem Informasi Manajemen Aset Tetap Pemerintah Kabupaten Poleweli Mandar Berbasis Website Menggunaka Qr-Code - Masita Masita; Basri Basri; Reski Idrus; Tajuddin Tajuddin (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2026)
Fixed asset management is a crucial component in supporting the performance of local governments. However, the Polewali Mandar Regency Government still faces obstacles in managing assets conventionally, such as the risk of recording errors, duplicate data, and difficulties in field data verification which is time-consuming. This study aims to design and build a Web-Based Fixed Asset Management Information System integrated with Quick Response Code (QR Code) technology as a digital solution for real-time asset data collection, tracking, and monitoring. The approach taken for system development is known as the Waterfall approach, encompassing the phases of analyzing requirements, system design, execution, evaluation, and ongoing support. The creation of the system was carried out utilizing the PHP coding language, the MySQL database system, and Tailwind CSS to achieve a mobile-friendly interface. Data collection techniques were conducted through observation, interviews, and literature studies at the General Affairs Division of the Regional Secretariat of Polewali Mandar Regency. The result of this research is a fixed asset management information system featuring the generation of unique QR Code labels for each asset, category and location management, and reporting features divided into three access levels: Admin, Operator, and Verificator. Based on the system testing results, an average score of above 4.00 was obtained for indicators of ease of use (user-friendly), access speed, and information accuracy. In conclusion, the implementation of this QR Code-based system is proven to increase the efficiency of the asset identification process in the field, minimize manual input errors, and improve accountability in regional asset management in Polewali Mandar Regency.